PERSAINGAN HARGA DALAM USAHA DAN PERAN KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) - Mustaming Mustaming (MUAMALAH, 2015)
The phenomenon that occurs in Indonesia are many practices unfair competition in a variety of industries with an agreement or agreements with other businesses with a variety opatterns. In addition these practices also involve other parties, namely the association and thegovernment. In the face of these cases required the role of the Business CompetitionSupervisory Commission (KPPU) to act firmly crack down on businesses that compete withunhealthy. But not only assertiveness necessary to create a conducive environment for doingbusiness, also needed a continuity and consistency of the Commission to enforce competitionlaw in Indonesia through the application of Law No. 5 1999.